2014
DOI: 10.1155/2014/425823
|View full text |Cite
|
Sign up to set email alerts
|

Dislocability of Localization Devices for Nonpalpable Breast Lesions: Experimental Results

Abstract: Purpose. For accurate resection of nonpalpable malignant breast lesions with a tumor-free resection rim, an exact and stable wire localization is essential. We tested the resistance towards traction force of different localization devices used in our clinic for breast lesions in two types of tissue. Materials and Methods. Eight different commercially available hook-wire devices were examined for resistance towards traction force using an analogue spring scale. Results. Most systems showed a high level of movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Wire movement in relation to clips and hooks was previously shown to relate to density of the tissue . Kaul et al found similar results in human, turkey, and pork tissue when they studied the movement of various wires in tissues designed to simulate fatty and dense breast tissue . In our study, the wire tended to move out of the fatty breast.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Wire movement in relation to clips and hooks was previously shown to relate to density of the tissue . Kaul et al found similar results in human, turkey, and pork tissue when they studied the movement of various wires in tissues designed to simulate fatty and dense breast tissue . In our study, the wire tended to move out of the fatty breast.…”
Section: Discussionsupporting
confidence: 81%
“…1,5,6 Kaul et al found similar results in human, turkey, and pork tissue when they studied the movement of various wires in tissues designed to simulate fatty and dense breast tissue. 1 In our study, the wire tended to move out of the fatty breast. Wire movement is more likely in larger breasts, especially when the wire is placed from a medial direction.…”
Section: Pathologic and Anatomic Characteristics Evaluated For Wirementioning
confidence: 83%
See 1 more Smart Citation
“…Overall, our results are in concordance with studies done in the past regarding the frequencies of different mammographic signs in the detection of breast carcinoma. Goedde et al, in his study, found that spiculated density was present in 44% cases, followed by clustered microcalcifications in 25%, mass in 22%, and asymmetric density in 14% of the cases [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Masroor, et al, 2012 (12) conducted WGL in 53% of the cases utilizing mammography guidance and 40% utilizing ultrasound guidance. Conversely, de Roos, et al, 2013 (13) reported that in their study, ultrasonography was used to aid localization in 72.6% of patients, mammography in 26.5%, and MRI in 0.9% of patients.…”
Section: Discussionmentioning
confidence: 96%